Distribusi dan Luas Stomata pada Enam Jenis Tanaman Dikotil - Rini Primawati; Entin Daningsih (Institut Pertanian Bogor, 2022)
Stomatal distribution and area are related to transpiration rate. This study measured stomatal distribution and area in dicotyledon plants used as ornamental plants. The study used Factorial Completely Randomized Design (CRD) with the main factors were six types of dicotyledon plants and three plant parts (top, middle and bottom). Combination factors were the interaction of plant species and parts. By using the replica method and micrometer, the study used five replications with the measured parameters: the stomatal distribution and area. Data were analyzed using SAS with the Factorial RAL model and continued with the LSD test if the treatments were significant. Correlation coefficients between stomatal distribution and area were calculated to see the relationship between the two. The types and plant parts significantly affected the stomatal distribution, while the stomatal area was influenced by the main and combination factors. Syzygium paniculatum Gaertn had the highest stomatal distribution and was different from other plant types. Meanwhile, lower leaves had the lowest stomatal distribution and differed from the middle and upper. Aerva sanguinolenta Bl had the highest stomatal area (591.05) compared to other plant species. The stomatal area on the plant's upper leaves (272,71) was significantly lower than the middle and lower parts. The combination between species and the lower part of the plant produced the highest stomatal area compared to other combinations. Stomatal distribution was inversely proportional to the stomatal area. Keywords: dicotyledon, part of plant, stomatal area, stomatal distribution